1989
DOI: 10.1002/ijc.2910430523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low‐ and high‐density lipoproteins on the proliferation of human breast cancer cells In vitro: Differences between hormone‐dependent and hormone‐independent cell lines

Abstract: The influence of low- and high-density lipoproteins on the proliferation of human breast cancer cells in culture was studied. We compared total cell number after incubation for 48 hr in culture medium containing or lacking plasma lipoproteins. Marked differences were found between hormone-dependent (MCF-7, T-47-D, ZR-75) and hormone-independent (MDA-MB-231, HBL-100) mammary tumor cell lines. The cells also reacted differently on the different lipoproteins offered in the medium. Human low-density lipoproteins (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 17 publications
5
46
0
1
Order By: Relevance
“…25 In vitro studies have shown that low serum HDL-C stimulates the growth of hormone dependent breast cancer cells. 23,24,26 Low serum HDL-C is independently associated with increased postmenopausal breast cancer risk among obese and overweight women. Furthermore serum HDL-C may be considered a marker of androgen status, because hormones finely tune the levels of serum HDL-C, by regulating the activity of the lipolytic enzyme hepatic lipase.…”
Section: Discussionmentioning
confidence: 99%
“…25 In vitro studies have shown that low serum HDL-C stimulates the growth of hormone dependent breast cancer cells. 23,24,26 Low serum HDL-C is independently associated with increased postmenopausal breast cancer risk among obese and overweight women. Furthermore serum HDL-C may be considered a marker of androgen status, because hormones finely tune the levels of serum HDL-C, by regulating the activity of the lipolytic enzyme hepatic lipase.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism was not clear, the data implied that HDL as well as LDL could be a source of CE for leukemic cells. A previous study in BrC cells showed that either HDL or LDL dose-dependently stimulated proliferation of ER-cell lines, but only HDL had the effect on ER+ cells lines (Rotheneder and Kostner 1989). In an animal model of PrC, a diet high in fat and cholesterol resulted in increased tumor incidence and increased tumor expression of scavenger receptor B1, the receptor responsible for selective uptake of HDL-C (the major form of circulating cholesterol in mice) by cells (Llaverias, Danilo et al 2010).…”
Section: Experimental and Mechanistic Evidence For Role Of Ldl In Cancermentioning
confidence: 94%
“…pronounced for oestrogen-receptor-positive cells as compared with oestrogen-receptor-negative cell lines [5].…”
Section: Introductionmentioning
confidence: 92%